2021
DOI: 10.1038/s41598-021-02651-y
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling and natural killer cell infiltration in tumor tissues underlie medulloblastoma prognosis

Abstract: Medulloblastoma is the most common embryonic brain tumor in children. We investigated a cohort of 52 Asian medulloblastoma patients aged between 0 and 19 years old, who received surgical resections and post-resection treatments in the Taipei Medical University Hospital and the Taipei Veterans General Hospital. Genome-wide RNA sequencing was performed on fresh-frozen surgical tissues. These data were analyzed using the CIBERSORTx immune deconvolution software. Two external clinical and molecular datasets from U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…We found 10 genes with DMPs that were conserved across subgroups suggesting a shared genetic background by subgroup may underlie some of the observed sexual dimorphism in medulloblastoma. Pathways identified within subgroups were largely signaling pathways including TGF-b, neurotrophic receptors, and NOTCH, which are known to impact prognosis in medulloblastoma and according to our findings may vary by sex within subgroups (34,47,48). Importantly, we identified four genes that housed sex-DMPs that also have chemotherapies available that could be studied in a sex-specific manner to improve outcomes for males and females with medulloblastoma.…”
Section: Discussionmentioning
confidence: 57%
“…We found 10 genes with DMPs that were conserved across subgroups suggesting a shared genetic background by subgroup may underlie some of the observed sexual dimorphism in medulloblastoma. Pathways identified within subgroups were largely signaling pathways including TGF-b, neurotrophic receptors, and NOTCH, which are known to impact prognosis in medulloblastoma and according to our findings may vary by sex within subgroups (34,47,48). Importantly, we identified four genes that housed sex-DMPs that also have chemotherapies available that could be studied in a sex-specific manner to improve outcomes for males and females with medulloblastoma.…”
Section: Discussionmentioning
confidence: 57%
“…NK cells can migrate to TME and exhibit cytolytic activity to kill tumor cells directly without specific immunization. NK cells were found to exist in MBs in the previous studies [ 44 , 52 , 53 , 54 ]. It was reported that NK cells can suppress SHH MB tumor growth in a Daoy xenografted mouse model [ 53 ].…”
Section: Discussionmentioning
confidence: 93%
“…This is often dependent on the cytokines secreted by the other immune cells into TME and also the tumor by itself which negatively contributes to NK cell activation status secreting for example TGFβ or IL-10. This favors a resting phenotype, frequently found in tumor tissues in association with poor prognosis [ 121 , 122 ].…”
Section: Natural Killer (Nk) Cells: Overviewmentioning
confidence: 99%